Direction of National Law Development Year 2005-2025 to Encounter the Age of 4.0 Industry Revolution - Prandy A.L. Fanggi; Safaruddin Efendi; Rengga Sandy Suranggana; Rosadi Purwohadi (Unram Law Review, 2019)
Aim of this research is to analyze the direction of national legal development in the period of 2005-2025 in order to address 4.0 industry revolution era. This research is applying normative research method and conceptual approach by mean of studying legal concept and theory supplemented with statute approach in order to analyze legal regulations related to this research. According to research result, national legal development 2005-2025 was not prepared to tackle 4.0 industry revolution era, since the direction national legal development substantially is not compatible and not comprehensive as legal development is positioned as the booster of national economy advancement in long-term development plan of 2005-2025.